2008
DOI: 10.1002/jcp.21651
|View full text |Cite
|
Sign up to set email alerts
|

Heterotypic interactions in the preservation of morphology and functionality of porcine hepatocytes by bone marrow mesenchymal stem cells in vitro

Abstract: Temporary replacement of specific liver functions with extracorporeal bioartificial liver has been hampered by rapid de-differentiation of porcine hepatocytes in vitro. Co-cultivation of hepatocytes with non-parenchymal cells may be beneficial for optimizing cell functions via mimicry of physiological microenvironment consisting of endogenous matrix proteins. However, the underlying mechanisms remain to be elucidated. A randomly distributed co-culture system composed of porcine hepatocytes and bone marrow mese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…A co-culture system of porcine hepatocytes and MSCs was prepared as described previously [14]. In brief, bone marrow was aspirated from the iliac crest of the pigs, then the mononuclear cells were collected over a Ficoll histopaque layer by gradient centrifugation (20 minutes, 400 g, density 1.077 g/ml) and seeded at a density of 1 × 10 6 cells/cm 2 in growth medium containing low-glucose DMEM supplemented with 10% FBS, 100 IU/ml penicillin and 100 mg/ml streptomycin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A co-culture system of porcine hepatocytes and MSCs was prepared as described previously [14]. In brief, bone marrow was aspirated from the iliac crest of the pigs, then the mononuclear cells were collected over a Ficoll histopaque layer by gradient centrifugation (20 minutes, 400 g, density 1.077 g/ml) and seeded at a density of 1 × 10 6 cells/cm 2 in growth medium containing low-glucose DMEM supplemented with 10% FBS, 100 IU/ml penicillin and 100 mg/ml streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…The bioreactor is composed of a stack of 65-layer round flat plates and a cylindrical container with an inlet on the top and an outlet on the bottom. A co-culture system of porcine hepatocytes and mesenchymal stem cells (MSCs), which had been established previously in our institute [14], was perfused into the bioreactor to act as functional cells, and a new extracorporeal BAL support system based on the novel multi-layer radial-flow bioreactor and the co-culture system of porcine hepatocytes and MSCs. was constructed.…”
Section: Introductionmentioning
confidence: 99%
“…Qihao et al showed the supportive effect of adult liver cells on hepatic differentiation of rat MSCs. They observed spheroid formation of the differentiated cells which could express liver specific markers such as albumin, α-fetoprotein and cytokeratin-18 at gene and protein levels [56]. Moreover, the heterotypic interaction of porcine hepatocytes/MSCs at ratio 2:1 was found as an optimal ratio for hepatic lineage induction.…”
Section: Induction By Soluble Growth Factors or Cytokines-defined Mediummentioning
confidence: 96%
“…Our investigations indicated that co-cultivation could promote the activities and functions of hepatocytes by forming spherical aggregates, increasing direct contact between the liver cells and other cells; co-cultured non-parenchymal cells can promote the liver cells' function. The component of the extracellular matrix secreted by non-parenchymal cells could provide a favorable growth microenvironment for hepatocytes [15][16][17][18][19].…”
Section: Cell Sourcesmentioning
confidence: 99%